Characteristic of Nasopharyngeal Carcinoma Patients in Mangusada General Hospital in January-December 2019 - I Gusti Ketut Nurada; I Gusti Ayu Putu Wahyu Widiantari (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharyngeal carcinoma is the most common head and neck malignancy worldwide, with a unique geographic distribution pattern. The incidence of NPC in Indonesia is 6.2 per 100,000 with 13,084 new cases and 7,391 deaths due to this disease in 2012, which places Indonesia as one of countries with numerous case of nasopharyngeal carcinoma and highest deaths in the world. Objective: The purpose of this study was to assess the characteristics of nasopharyngeal carcinoma patients at Mangusada General Hospital including histopathological classification, distribution according to age and sex, as well as clinical signs and symptoms. Methods: The descriptive study with a retrospective cross-sectional approach to assessing the entire population of nasopharyngeal carcinoma in Mangusada General Hospital based on gender, age, symptoms, and histopathological classification from January to December 2019. The data was obtained from medical records and processed into frequency and distribution table. Results: The number of cases that obtained was 40 cases. There were more male than female nasopharyngeal carcinoma patients with a sex ratio of 1.66, and found mostly in the age group 45-64 years (67.5%). Most of the patients presented with advanced complaints such as nasal congestion (60%), bleeding from the nose (57.5%), and lumps in the neck (55%). The most histopathologic type of nasopharyngeal carcinoma found was the non-keratinizing squamous cell carcinoma undifferentiated subtype (100%). Conclusion: All patients with nasopharyngeal carcinoma who came to the Mangusada General Hospital were histopathologically included non-keratinizing squamous cell carcinoma undifferentiated subtype, with the largest age distribution in the early elderly group, the most affected patients were male, and most patients who attended already showing advanced clinical signs.